A novel approach for the production of human recombinant BMP-2 for bone tissue engineering applications - Bessa, Paulo C. (2006)
Bone tissue engineering has been an increasing field of research during the last years. The ideal approach for a regenerative application would consist in the use of cells from the patient, scaffolding materials and differentiation growth factors. Bone morphogenetic protein-2 (BMP-2) is one such growth factors with a strong ability to induce new bone and cartilage formation and has been used as a powerful osteoinductive component of several late-stage tissue engineering products for bone grafting. In this work, we aimed at obtaining high yields of human recombinant BMP-2 in a stable, pure and biologically active form by use of a new bacteria expression system that circumvents the disadvantages of conventional recombinant protein preparation methods and to perform a study of the stability conditions and the functionality of these peptides in vitro in human mesenchymal stem cells and C2C12 murine cell line.